1976
DOI: 10.1113/jphysiol.1976.sp011438
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐secretion coupling: role of cyclic AMP, cyclic GMP and calcium in mediating enzyme (kallikrein) secretion in the submandibular gland.

Abstract: SUMMARY1. The role of adenosine 3':5'-phosphate (cyclic AMP) and guanosine 3': 5'-phosphate (cyclic GMP) as second messengers for the enzyme secretary response evoked by the autonomic neurotransmitters, noradrenaline and acetylcholine, is examined in this in vitro study on the guinea-pig submandibular gland.2. Noradrenaline increased enzyme (kallikrein) secretion. The initial stimulation of enzyme release appeared to be dose-dependent. The time course of cumulative kallikrein secretion revealed a complex patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Nevertheless, such interactions are likely to occur in life (see Emmelin, 1987). Work by Albano, Bhoola, Heap & Lemon, (1976) on guinea-pig submandibular glands indicated that the pharmacological stimulation of kallikrein secretion involved fl-adrenergic mechanisms as well as a-adrenergic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such interactions are likely to occur in life (see Emmelin, 1987). Work by Albano, Bhoola, Heap & Lemon, (1976) on guinea-pig submandibular glands indicated that the pharmacological stimulation of kallikrein secretion involved fl-adrenergic mechanisms as well as a-adrenergic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Procion yellow moves more irregularly in situ (Kaneko, 1971) or in vitro (Johnson & Sheridan, 1971 (Butcher, 1975;Schultz, Hardman, Shultz, Baird & Sutherland, 1973) which may play some role in determining the major differences in type of secretion elicited by the two nerve inputs. fl-Adrenoceptor agonists, which cause an increase in cyclic AMP (Bdolah & Schramm, 1965;Albano et al 1976), produce saliva with a greater protein content (Schramm, 1973). Cholinergic drugs, which cause an increase in cyclic GMP in the presence of phosphodiesterase inhibitors (Schultz et al 1973;Albano et al 1976), produce a more watery saliva (Schneyer et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…fl-Adrenoceptor agonists, which cause an increase in cyclic AMP (Bdolah & Schramm, 1965;Albano et al 1976), produce saliva with a greater protein content (Schramm, 1973). Cholinergic drugs, which cause an increase in cyclic GMP in the presence of phosphodiesterase inhibitors (Schultz et al 1973;Albano et al 1976), produce a more watery saliva (Schneyer et al 1972). In contrast to in vitro experiments, however, Muir & Templeton (1976) …”
Section: Discussionmentioning
confidence: 99%
“…However, Diamond & Hartle (1976) have shown that cyclic GMP levels in guinea-pig taenia coli increase after the contractile response to cholinergic stimulation and not before, arguing against an involvement of the nucleotide. In the salivary gland, too, the role of cyclic GMP in secretion is not very clear (Albano et al, 1976;Durham, Butcher, Muir & Templeton, 1977) Jenkinson & Koller (1977) to explain the potentiation of an a-adrenergic response by phosphodiesterase inhibitors in guinea-pig liver slices. However, it is worth pointing out that in the present work 3 chemically distinct phosphodiesterase inhibitors have been used and while they could produce potentiation of parasympathetic vasodilatation via cyclic AMP in the manner suggested above, it seems less likely that other non-specific actions of the inhibitors are responsible.…”
Section: Role Of Cyclic Nucleotidesmentioning
confidence: 99%
“…Certainly #-receptor stimulation leads to an increase in adenylate cyclase activity (see Butcher, Goldman & Nemerovski, 1976) and cyclic AMP concentration (see Albano, Bhoola, Heap & Lemon, 1976) in the whole gland but experiments so far have been concerned with secretory activity, not the control of blood flow.…”
Section: Introductionmentioning
confidence: 99%